PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, INTENSITAS MODAL DAN LIKUIDITAS TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study examines the effect of profitability, leverage, size, capital intensity and liquidity of the accounting conservatism on the real estate and property companies listed on the Indonesia Stock Exchange. This study used purposive sampling method in sample selection, the criteria for a sample of the real estate and property companies listed in Indonesia Stock Exchange (IDX) during the period 2010-2013. Based on these criteria, obtained a sample of 188 companies over a four-year observation period. Or influence the relationship between variables and is described by using logistic regression analysis. The results showed that the variable profitability and capital intensity and a significant positive effect on the variable accounting conservatism. Variable leverage and liquidity variables and no significant negative effect on accounting conservatism. And variable positive effect size was not significant.Keywords: Conservatism in Accounting, Profitability, Leverage, Company Size, Capital Intensity, and Liquidity